2012
DOI: 10.1038/nchembio.766
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific non–reducing end carbohydrate biomarkers for mucopolysaccharidoses

Abstract: A significant need exists for improved biomarkers for differential diagnosis, prognosis and monitoring of therapeutic interventions for mucopolysaccharidoses (MPS), inherited metabolic disorders that involve lysosomal storage of glycosaminoglycans. Here, we report a simple reliable method based on the detection of abundant non-reducing ends of the glycosaminoglycans that accumulate in cells, blood, and urine of MPS patients. In this method, glycosaminoglycans were enzymatically depolymerized releasing unique m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 42 publications
(56 reference statements)
4
145
0
Order By: Relevance
“…In 2012, Lawrence et al showed that another new method with enzyme digestion can detect DS and HS by analysis of non-reducing ends of urinary GAGs by LC-MS/MS. Currently, this method does not provide a measure of non-reducing ends for KS [51]. Overall, establishment of methods to measure disaccharides makes it feasible to interpret individual GAG values, leading to feasible and accurate diagnosis, prognosis, and monitoring therapies for MPS.…”
Section: History Of Gag Assay By Tandem Mass Spectrometry (Ms/ms)mentioning
confidence: 99%
“…In 2012, Lawrence et al showed that another new method with enzyme digestion can detect DS and HS by analysis of non-reducing ends of urinary GAGs by LC-MS/MS. Currently, this method does not provide a measure of non-reducing ends for KS [51]. Overall, establishment of methods to measure disaccharides makes it feasible to interpret individual GAG values, leading to feasible and accurate diagnosis, prognosis, and monitoring therapies for MPS.…”
Section: History Of Gag Assay By Tandem Mass Spectrometry (Ms/ms)mentioning
confidence: 99%
“…Urinary GAGs and specific lysosomal enzymes have been the only biomarkers for MPS, although recent studies identified serum heparin cofactor II-thrombin (HCII-T) as a biomarker for MPS I, II, and III; 34 dipeptidyl peptidase IV (DPP-IV) for MPS I, II, III, IVA, and VI; 35 and recently the potential of disease-specific non-reducing end carbohydrate biomarkers for MPS. 36 However, there are currently no specific biomarkers for MPS corresponding to neurological disease severity or therapeutic responsiveness. The critical challenge for finding CNS-specific biomarkers stems from limited access to the CNS tissues of patients, especially at early disease stages.…”
Section: Mucopolysaccharidosis (Mps) Iiib (Online Mendelian Inheritanmentioning
confidence: 99%
“…Thus, GRIL-LC/MS provides a way to determine not only the disaccharide composition of GAG chains, but also the total amount of GAG in a sample. Analysis of GAGs from MPS patients demonstrated the utility of GRIL-LC/MS for determining total storage and uncovered one or more additional peaks of [ 12 C 6 ]anilinetagged material that varied in elution position and mass dependent upon the MPS disorder [18]. Mass spectral analysis revealed that the additional peaks were derived from the nonreducing end of GAG chains.…”
Section: Sensi-pro Assaymentioning
confidence: 99%
“…In this review, we summarize various approaches to glycan-based biomarker development for MPS with a discussion of a new approach that has identified unique glycan NRE biomarkers [18]. We refer the reader to other recent reviews that cover other types of biomarkers based on enzyme mass, enzyme activity and pathological consequences of disease [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%